Memberdayakan Inovator Masa Depan: Memanfaatkan Pembelajaran Berbasis Proyek dan AI untuk Meningkatkan Pemikiran Analitis, Kreativitas, dan Kolaborasi dalam Menjelajahi Sistem Peredaran Darah di SMAN 1 Kota Magelang - Muhammad Khoirul Antony; Sendy Putra Pradana; Ahmad Naharuddin Ramadhan; Susi Dewiyeti; Ermia Hidayati (Postgraduate, University of Mataram, 2025)
Modern learning focuses on active student engagement through thinking, creativity, and collaboration, supported by PjBL and AI to suit the digital era. This study explores the impact of AI-assisted project-based learning (PjBL) on students' analytical thinking, creative thinking, and collaboration skills in biology education, focusing on the circulatory system. Using a quasi-experimental design with 80 eleventh-grade students (40 experimental, 40 control) from SMAN 1 Magelang, Indonesia, the research employed MANOVA and ANOVA to analyze posttest scores. Results revealed significant improvements in the experimental group, with mean differences of 5.67 (analytical thinking, *p* = 0.001), 4.12 (creative thinking, *p* = 0.010), and 3.89 (collaboration, *p* = 0.015). AI tools enhanced analytical skills through data visualization and feedback, fostered creativity via simulations and iterative problem-solving, and supported collaboration via AI-driven task allocation and communication platforms. However, collaboration gains were more modest, underscoring the enduring role of interpersonal dynamics. The study concludes that integrating AI into PjBL effectively cultivates higher-order thinking skills, though its implementation requires balancing technological and human-centric pedagogical approaches. These findings advocate for AI as a transformative tool in biology education, provided ethical and accessibility considerations are addressed.